Digital Marketing for Russian Market. Case: Wild Taiga - Khmelevskoy, Sergey (Kajaanin ammattikorkeakoulu, 2015)
The thesis is aimed to develop suitable digital marketing strategy for Wild Taiga in order to target the Russian tourists efficiently, using different marketing tools based on integrated marketing communications principle. Effort have been made for practical orientation of this project with a strong theoretical part and analytical thinking. Theoretical framework includes analysis of digital marketing in contexts of tourism as well as Wild Taiga network. In order to discover the efficient tools in real life contexts, current usage of digital media by Russians was analysed. Prerequisite for the project is a highly volatile situation on the Russian tourism market. The research have been conducted to discover the needs and preferences on a target audience. The research data was analysed and appropriate manners have been made to adjust the digital marketing plan according to the findings. As the result, destination marketing organization will be able to penetrate Russian marketing through digital media and start presence in Russian-speaking social media. Some important starting materials for a digital marketing campaign, such as semantic core and VK layout, was created in order to estimate the outcomes and measure KPI’s.